Consensus recommendations on therapeutic hypothermia after minimally invasive intracerebral hemorrhage evacuation from the hypothermia for intracerebral hemorrhage (HICH) working group - Baker, Turner S.; Kellner, Christopher P.; Colbourne, Frederick; Rincon, Fred; Kollmar, Rainer; Badjatia, Neeraj; Dangayach, Neha; Mocco, J.; Selim, Magdy H.; Lyden, Patrick; Polderman, Kees; Mayer, Stephan (Frontiers in Neurology, 2022)
Background and purpose Therapeutic hypothermia (TH), or targeted temperature management (TTM), is a classic treatment option for reducing inflammation and potentially other destructive processes across a wide range of pathologies, and has been successfully used in numerous disease states. The ability for TH to improve neurological outcomes seems promising for inflammatory injuries but has yet to demonstrate clinical benefit in the intracerebral hemorrhage (ICH) patient population. Minimally invasive ICH evacuation also presents a promising option for ICH treatment with strong preclinical data but has yet to demonstrate functional improvement in large randomized trials. The biochemical mechanisms of action of ICH evacuation and TH appear to be synergistic, and thus combining hematoma evacuation with cooling therapy could provide synergistic benefits. The purpose of this working group was to develop consensus recommendations on optimal clinical trial design and outcomes for the use of therapeutic hypothermia in ICH in conjunction with minimally invasive ICH evacuation. Methods An international panel of experts on the intersection of critical-care TH and ICH was convened to analyze available evidence and form a consensus on critical elements of a focal cooling protocol and clinical trial design. Three focused sessions and three full-group meetings were held virtually from December 2020 to February 2021. Each meeting focused on a specific subtopic, allowing for guided, open discussion. Results These recommendations detail key elements of a clinical cooling protocol and an outline for the roll-out of clinical trials to test and validate the use of TH in conjunction with hematoma evacuation as well as late-stage protocols to improve the cooling approach. The combined use of systemic normothermia and localized moderate (33.5°C) hypothermia was identified as the most promising treatment strategy. Conclusions These recommendations provide a general outline for the use of TH after minimally invasive ICH evacuation. More research is needed to further refine the use and combination of these promising treatment paradigms for this patient population.